2022
DOI: 10.15789/1563-0625-poa-2465
|View full text |Cite
|
Sign up to set email alerts
|

Profile of antiphospholipid antibodies and complement system in COVID-19 patients of different severity

Abstract: COVID-19, a severe acute respiratory syndrome caused by SARS-CoV-2, may predispose to thrombotic events, especially when combined with antiphospholipid antibodies (aPL). However, there are limited data on prevalence and antigenic specificity of aPL in COVID-19. Complement activation is assumed to play an important role in pathogenesis of COVID-19-associated coagulopathy. During the SARS-CoV-2 pandemic, it is necessary to identify important biomarkers for predicting severe course of COVID-19 and risk of thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The post-COVID-19 patients more often had elevated levels of anti-PE and anti-An V IgG, as well as higher median levels of anti-PE IgG and anti-PS/PT IgM, compared to the patients without a history of COVID-19. These results are consistent with the data from a previous study demonstrating a low detection rate of “criterial” aPL and higher incidence of “non-criteria” aPL, in particular antibodies to An V and PT, in patients with COVID-19 [ 35 ]. The development of pro-inflammatory and pro-thrombotic conditions and the dysfunction and damage of vascular endothelial cells in COVID-19 lead to the exposure of negatively charged phospholipids, in particular PS, on the surface of activated and damaged cells, and the subsequent formation of complexes of phospholipids with phospholipid-binding proteins, such as An V and PT; this, in turn, promotes the production of autoantibodies to An V, PT, and PS/PT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The post-COVID-19 patients more often had elevated levels of anti-PE and anti-An V IgG, as well as higher median levels of anti-PE IgG and anti-PS/PT IgM, compared to the patients without a history of COVID-19. These results are consistent with the data from a previous study demonstrating a low detection rate of “criterial” aPL and higher incidence of “non-criteria” aPL, in particular antibodies to An V and PT, in patients with COVID-19 [ 35 ]. The development of pro-inflammatory and pro-thrombotic conditions and the dysfunction and damage of vascular endothelial cells in COVID-19 lead to the exposure of negatively charged phospholipids, in particular PS, on the surface of activated and damaged cells, and the subsequent formation of complexes of phospholipids with phospholipid-binding proteins, such as An V and PT; this, in turn, promotes the production of autoantibodies to An V, PT, and PS/PT.…”
Section: Discussionsupporting
confidence: 93%
“…According to a systematic review [ 36 ], such antibodies to the PS/PT complex were found in 0–24% of patients with COVID-19 and antibodies to An V were found in 3–19% of similar patients. It has been suggested that antibodies to PT and An V may be involved in the pathogenesis of COVID-19-associated coagulopathy, transiently increasing at a later stage of the disease or causing COVID-19-induced APS in susceptible patients and convalescents [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%